2012
DOI: 10.1121/1.4765074
|View full text |Cite
|
Sign up to set email alerts
|

Signal-to-noise ratio adaptive post-filtering method for intelligibility enhancement of telephone speech

Abstract: Post-filtering can be utilized to improve the quality and intelligibility of telephone speech. Previous studies have shown that energy reallocation with a high-pass type filter works effectively in improving the intelligibility of speech in difficult noise conditions. The present study introduces a signal-to-noise ratio adaptive post-filtering method that utilizes energy reallocation to transfer energy from the first formant to higher frequencies. The proposed method adapts to the level of the background noise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Methods based on post-filtering (e.g. Hall and Flanagan, 2010;Jokinen et al, 2012) might achieve similar effects in terms of reallocating energy across frequencies. While the frequency response of the filter in Jokinen et al (2012) is close to the static weighting found in the current study (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Methods based on post-filtering (e.g. Hall and Flanagan, 2010;Jokinen et al, 2012) might achieve similar effects in terms of reallocating energy across frequencies. While the frequency response of the filter in Jokinen et al (2012) is close to the static weighting found in the current study (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…it tends to be flat after approximately 1.5 kHz), the filter proposed in Hall and Flanagan (2010) has an incremental response from approximately 0.4 to 3.5 kHz, which then holds constant thereafter 3.5 kHz. By comparing the performance of the two filters, Jokinen et al (2012) demonstrated that the filter with nearly equal frequency response for mid-high frequencies is more efficient than that with an incremental response in increasing narrowband (up to 4 kHz) intelligibility for listeners, especially in more severe conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several earlier studies showed that the performance of speech and speaker recognition systems decreased when processing telephone-quality signals comparing to systems utilizing high-quality recordings [8]. However, more recent studies highlighted the real possibility for cost-effective remote detection and assessment of voice pathology over telephone channels reaching normal/pathological voice classification accuracy close to 90 % [6,[9][10][11].…”
Section: Introductionmentioning
confidence: 95%